Women’s Labour in Movement. From Servants and Housewives to Racialised Domestic and Care Workers - Miranda Mora, Ana Maria (Las Torres de Lucca. International Journal of Political Philosophy, 2025)
This paper examines migrant women’s labour and the location of poor and racialised working women in the context of the contemporary care crisis. In the first part, I briefly reconstruct, the feminist critiques of the Marxist capitalist social (re)production theory and, the Decolonial and Postcolonial feminist criticisms of the Marxist universal model of the capitalist mode of (re)production and its conceptualisation of marginalised and excluded subjects. This analysis sets the ground for understanding the debts and innovations of Marx’s political economy operated by the contemporary theory of care. In the second part, I focus on the embodied and affective experiences of poor, black, brown, and indigenous women to identify concrete mechanisms and relations of exploitation, oppression, and violence produced in the migration process to maintain global care chains. I base my analysis on a review of case studies of Mexican, Indian, and Filipina migrant women. Finally, I highlight the inherent ambivalences of global care chains as a process of both neo-colonial feminisation of migration and reproduction of neoliberal capitalism and as a shared context of struggle and resistance grounded in embodied and affective experiences. Keywords: feminisation of migration, reproductive labour, global care chains, racialized working women